Prevalence of on-host ticks (Acari: Ixodidae) in small mammals collected from forest near to human vicinity in Selangor, Malaysia - Ishak, Siti Nabilah; Yusof, Muhammad Afif; Md-Nor, Shukor; Mohd Sah, Shahrul Anuar; Lim, Fang Shiang; Khoo, Jing Jing; Mohd-Taib, Farah Shafawati (Systematic and Applied Acarology Society, 2018)
Ticks are important vectors that transmit a variety of pathogenic microorganisms known to be medically important worldwide. Many vertebrate groups have become host to this organism, and their presence and abundance are an indicator of the condition of both host and its habitat. This study was conducted to determine tick's infestation and its prevalence on small mammal's residing in the recreational forests (RF) and semi-urban (SU) residential areas which have encountered Leptospirosis outbreak and cases in Hulu Langat, Selangor Malaysia. Trapping of the small mammals involved deploying two hundred cage traps in a systematic one-hectare plot (100 m × 100 m), as well as along the stream and forest trails at random. Ticks were extracted from the captured individual hosts. Identification of the tick species was performed based on morphological features and molecular approach using 16S rDNA and COI (cytochrome oxidase subunit I) genes. A total of 278 individuals of small mammals belonging to 15 species (13 Rodentia, 1 Scandentia and 1 Insectivora) were captured in the study areas. From these, 34 individuals from eight small mammal species were infested with ticks. The most infested host species was Muller's giant Sunda rat (Sundamys muelleri) with 5.80% (n=16). Ticks prevalence was slightly higher in RF with 6.40% (n=18) compared to SU with 5.80% (n=16). A total of 107 adult ticks (103 female and 4 male) were collected from the infested host. Ixodes granulatus was the most dominant tick species encountered (70.40%, n=85), followed by Dermacentor sp. (18.60%, n=20), while Amblyomma sp. was the least abundant (2%, n=2). This study provides information on tick species present and tick burden on small mammal hosts within the study areas. Our findings suggest that the visitors to the recreational forests and the residents of the semi-urban area were not only exposed to Leptospirosis bacteria but also tick bites and potentially tick-borne disease, therefore, precaution should be taken to avoid contact with small mammal hosts.